The Relationship between Paramedic Competency, Teamwork and Career Development with Quality of Service at Mengwi I Community Health Centre - Alit Naya; Luh Seri Ani; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2014)
Background and objective: Recent survey indicated that patient opinion of services at Mengwi I Community Health Centre was low and there was noticeable decline in patient visits. This study aims to investigate the issues related to the quality of health services given by the paramedics. Methods: A cross sectional study was conducted with 38 paramedics on duty at the outpatient unit. They were interviewed to obtain the data on their opinions about the quality of their service, competence, teamwork and career development opportunities. Chi square test was used for bivariate analysis and logistic regression for multivariate analysis. Results: The results of bivariate analysis indicated there was significant association between the paramedics’ quality of service with the competence, teamwork and career development (p<0,001). Multivariate analysis indicated that the paramedics’ competence (p=0,035) and development of career (p=0,042) are related to the paramedics’ quality ofservice. Conclusion: The quality of service of paramedics at Mengwi I Community Health Centre with the paramedics’ competence and development of career.